Educação inclusiva: o processo de socialização na busca por uma educação para todos - Gomes, Bianca Batista Ribeiro (Universidade Federal do Tocantins, 2022)
This study is a theoretical research about inclusive education with the main objective of discuss the socialization process in the view of Education for all. The specific objectives were: identify inclusive education as a social process and describe the importance of socialization in inclusive education. The methodology used for this study is based on bibliographic, qualitative and descriptive research. Authors such as Beyer (2013), Gubany (2008), Mittler (2003), Oliveira & Profeta (2011), Pacheco (2007), among others, were taken as theoretical basis. This research aims to create or expand a more critical and conscious field of view regarding the concept of inclusion, to present data on the inclusion of Basic Education released by INEP in 2020 so that it is really possible for us to consolidate a equipotent and fairer education for all.